Evaluation and genetic analysis of coal structures in deep Jiaozuo Coalfield, northern China: Investigation by geophysical logging data. (1st December 2017) - Hou, Haihai; Shao, Longyi; Guo, Shuangqing; Li, Zhen; Zhang, Zhijie; Yao, Minglei; Zhao, Sheng; Yan, Chunzhong
Abstract: Coal structure determines the porosity and permeability in coal reservoirs to a great extent, which not only influences the evaluation of coalbed methane (CBM) reservoirs, but is also closely related to their production efficiency. The traditional methods for identifying coal structure mainly depend on coals in boreholes or underground roadway sections. However, as these methods are expensive and limited to certain conditions, the geophysical logging data have been proven recently to be effective for detecting coal structure in boreholes. The Machang exploration block is situated in the southeastern (deep-seated) part of the Jiaozuo Coalfield, northern China, and the coals in this block have a higher gas content ranging from 25 m 3 /t to 40 m 3 /t but are typified with complex coal structures. Based on the field observation of coal structures for a cumulative length of 447.5 m of cores from the 75 boreholes in the Machang block, the cut-off values of the logging data for quantitatively identifying coal structures (including lump coal, lump-powder coal and powder coal) were established using the three well-logging curves of deep lateral resistivity (LLD), gamma-gamma log (GGL) and natural gamma (GR). Subsequently, the relationships of coal structure with the corresponding coal depth, thickness, coal petrology, pore structures were investigated. Finally, the favorable areas for CBM exploration were evaluated according to the distribution of lump, lump-powder and powder coals. The results show that each coal structure has different logging characteristics, with lump coals showing lower GGL, higher GR and LLD, lump-powder coals of medium GGL, GR and LLD, while powder coals showing higher GGL, lower GR and LLD. The coal seam is composed of one to six sub-layers vertically, with a typical combination of powder coals on the top and bottom of the 21 coal seam, with lump coals or lump-powder coals in the middle part. Regional faults play a dominant role in controlling the distribution of coal structures, with the thickness of powder coals decreasing rapidly with increasing distance from faults. Furthermore, thicker or thinner coal seams also can result in a greater degree of damage during coal deformation. From lump coals to powder coals, the vitrinite content, maximum vitrinite reflectance (Ro, max ), specific surface area and total pore volume show an upward trend but the average pore size shows a downward trend. The 4 types and 13 sub-types of coal structures were divided based on the established ternary diagram. The central parts in the South and Middle areas, together with the southwestern part of the North area in the Machang exploration block are determined to be the best regions for CBM production.